Implikasi Pemanfaatan Lahan terhadap Tingkat Keanekaragaman Jenis Tanaman di Kawasan Kabupaten Kuningan Jawa Barat - Kris Tiyanto; Andrianto Kusumoarto (Fakultas Biologi | Universitas Jenderal Soedirman, 2021)
The plant diversity has become of one indicated maintained, preserved and it has impact to environmental quality, and of course has value to human wellbeing dimension, which it has used to a demand of living the human. Beside of plant diversity has key a role of important in preserving of natural system condition by sustainable. Therefore aim this study to know how the plant diversity (H’), therefor methods which is used to vegetation analyses, by the plotting of sample area is 20x20 m, which are 3 subdistrict in Kuningan district area as representative of research samples methods. This result of research has inventories at least ±43 plants species in all area research, in which every area has had difference of index plant diversity level, in which Kadugede subdistrict area has highest level, than one the other subdistrict area, which is value H’= 2.30, and the lower of diversity index value is Cimahi H’= 1.49 and Ciawegebang H’= 1.14 level. Preserving and maintaining of plant diversity is one of all ways or strategies to increasing of quality ecosystem or carrying capacity and its conservation goals of sustainable developing in urban or rural area.